Propuesta para la evaluación de revistas y la investigación en ciencias sociales y humanidades en Colombia: una mirada desde las métricas Dialnet - Gregorio-Chaviano, Orlando; Jiménez-Contreras, Evaristo (Revista Científica, 2024)
Like in other countries, the current landscape of scientific evaluation in Colombia faces challenges in studying the social sciences and humanities. The coverage limitations of citation databases, the scant presence of Colombian journals in them, and issues with existing classifications justify the creation of products that cover aspects not present in international indices and that allow evaluating the national production and its contributors. This article presents, based on a sample of education journals, the methodology for creating a citation-based tool that is useful for obtaining indicators and descriptions of journals and scientific activity at various levels. This initiative is based on the Spanish proposal Dialnet Métricas, already active in most areas of social sciences, humanities, and law, as well as on the interest it represents for Colombia to have a tool that allows analyzing journals beyond the fulfillment of criteria and provides indicators that contribute to the evaluation of science. This work outlines the process of journal selection, the management of the source data used, a citation analysis, and a description and visualization of the indicators. The value and contributions of the tool in the Colombian context are confirmed through the obtainment of citations and indicators for a considerable number of national journals and through their comparison with Publindex.